2022
DOI: 10.3389/fendo.2022.967822
|View full text |Cite
|
Sign up to set email alerts
|

An integrated RNA sequencing and network pharmacology approach reveals the molecular mechanism of dapagliflozin in the treatment of diabetic nephropathy

Abstract: Dapagliflozin, an inhibitor of sodium-glucose cotransporter 2 (SGLT2), is a new type of oral hypoglycemic drugs which can promote glucose excretion in the kidney. Studies have shown that dapagliflozin has renoprotective effect in the treatment of type 2 diabetes. However, the underlying mechanism remains unclear. Here, we combined integrated RNA sequencing and network pharmacology approach to investigate the molecular mechanism of dapagliflozin for diabetic nephropathy (DN). Dapagliflozin significantly relieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Many studies have shown that complement C3 levels were higher in multiple metabolic diseases, including obesity, diabetes, and NAFLD, and an energy-restricted diet decreased plasma C3 levels in men with obesity [ 39 42 ]. A recent study found that dapagliflozin treatment decreased mRNA and protein expression of C3 in the kidney of the db/db mice [ 43 ]. These changes in proteins might be associated with the beneficial effect of dapagliflozin on cardiovascular and renal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that complement C3 levels were higher in multiple metabolic diseases, including obesity, diabetes, and NAFLD, and an energy-restricted diet decreased plasma C3 levels in men with obesity [ 39 42 ]. A recent study found that dapagliflozin treatment decreased mRNA and protein expression of C3 in the kidney of the db/db mice [ 43 ]. These changes in proteins might be associated with the beneficial effect of dapagliflozin on cardiovascular and renal outcomes.…”
Section: Discussionmentioning
confidence: 99%